Mewujudkan Semarang Hebat melalui Smart City (Studi Kasus pada Dimensi Smart Economy Kota Semarang) - Dimas Anugrah Dwi Saputra; Kismartini Kismartini; Ida Hayu Dwimawanti; Teuku Afrizal (PERSPEKTIF, 2022)
Smart City is a concept to shape a city for the better and can improve the welfare of its people. One of the dimensions in the implementation of Smart City is a smart economy that focuses on managing the development of economic growth that starts with innovations to increase competitiveness and open new business opportunities. Semarang city is one of the cities in Indonesia that has been implementing this concept since 2013 and its implementation was awarded Best Smart economy City in 2018. The methodology used is qualitative descriptive with primary data collection techniques with interview techniques and secondary data with literature study techniques. The implementation of the smart economy in Semarang City has three important aspects, namely Industry, Transaction, and Welfare. These three aspects are integrated into the indicators of the Semarang Hebat Priority Program which 6 indicators of 10 indicators. In this article, the author explains the implementation of the achievements of the smart economy in the city of Semarang based on the indicators of the Semarang Hebat Priority Program. In this article, the author explains the implementation of the smart economy in the city of Semarang based on the indicators of the Semarang Hebat Priority Program. The implementation of the smart economy in Semarang City has been running by showing a positive trend, with constraints from external factors in the form of the Covid-19 Pandemic. It is hoped that the Semarang City Government can maximize and improve sectors that show positive trends and anticipate unexpected conditions in the future.